2015
DOI: 10.2527/jas.2014-8368
|View full text |Cite
|
Sign up to set email alerts
|

Residual feed intake and blood variables in young Nellore cattle

Abstract: This study was conducted to evaluate associations of performance traits, feed efficiency, and blood variables with residual feed intake (RFI) in growing Nellore cattle. A total of 118 growing Nellore animals, 62 males and 56 females, were used. A diet containing 2 Mcal/kg was offered ad libitum and individual DMI was measured over a period of 84 d. Animals were classified as low (≤0.128 kg/d; = 40), medium (-0.128 to 0.135 kg/d; = 42), or high RFI (>0.135 kg/d; = 36). Blood samples were collected at the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
11
24
0
Order By: Relevance
“…well with the 19% differences in the Murrah buffalo calves divergently selected for low (-0.14 kg/d) and high RFI (0.14 kg/d), with no difference in body weight gain (SHARMA et al, 2016). NASCIMENTO et al (2015) noted that low RFI (≤0.128 kg/d) Nellore cattle consumed 7.2 kg DM/d, which was 14.0% less feed than animals with high RFI (>0.135 kg/d), although no significant differences in ADG were observed among RFI classes. A 10% reduction in DMI by the low RFI Murrah buffalo calves compared to high RFI (-0.20 vs. 0.23 kg DM/d), despite no differences in body weight gain, was reported by BOSE et al (2014).…”
Section: A K Singh Et Al: Efficiency Of Calves Varying In Rfisupporting
confidence: 55%
See 2 more Smart Citations
“…well with the 19% differences in the Murrah buffalo calves divergently selected for low (-0.14 kg/d) and high RFI (0.14 kg/d), with no difference in body weight gain (SHARMA et al, 2016). NASCIMENTO et al (2015) noted that low RFI (≤0.128 kg/d) Nellore cattle consumed 7.2 kg DM/d, which was 14.0% less feed than animals with high RFI (>0.135 kg/d), although no significant differences in ADG were observed among RFI classes. A 10% reduction in DMI by the low RFI Murrah buffalo calves compared to high RFI (-0.20 vs. 0.23 kg DM/d), despite no differences in body weight gain, was reported by BOSE et al (2014).…”
Section: A K Singh Et Al: Efficiency Of Calves Varying In Rfisupporting
confidence: 55%
“…Similar to the findings of the present study, PAULA et al (2013) and observed a negative correlation (r = -0.45) between RFI and the mean concentration of serum creatinine, and a comparison of the two RFI groups showed significant differences for this variable. However, no differences in the levels of blood creatinine between the low and high RFI groups were observed by SHARMA et al (2016) andBOSE et al (2014) in Murrah buffalo calves, or by NASCIMENTO et al (2015) in Nellore cattle.…”
Section: A K Singh Et Al: Efficiency Of Calves Varying In Rfimentioning
confidence: 72%
See 1 more Smart Citation
“…Kelly et al (2010b) and Nascimento et al (2015) found that insulin may affect feed efficiency, but we found no changes when we examined measures related to glucose metabolism, such as glucose and insulin, which might be related to a decrease in insulin sensitivity in muscle tissue of energetically inefficient animals (Richardson et al, 2004;Brown, 2005). Considering variability of insulin sensitivity, we do not suggest the use of insulin or glucose as indicators of RFI.…”
Section: Feeding Behaviors Between Divergent Rfi Groupsmentioning
confidence: 94%
“…In accordance with the present findings, Kelly et al (2010a) reported that systemic IGF-1 in yearling Limousin × Holstein-Friesian heifers was not related to RFI, as did Kundu et al (2014). Conversely, IGF-1 was determined to be genetically correlated in a positive manner with RFI in growing bulls (Moore et al, 2005) and Nellore cattle (Nascimento et al, 2015). The likely explanation for this inconsistency is that, in most studies to date in which IGF-I was correlated with RFI, the animals were measured at a young age shortly after weaning (Moore et al, 2005), animals were consuming a roughage-based diet (Brown, 2005), and consequently, animals might be expected to have a greater rate of lean tissue gain and reduced carcass fatness.…”
Section: Feeding Behaviors Between Divergent Rfi Groupsmentioning
confidence: 99%